Robotically assisted mitral valve repair using the butterfly technique in a patient with a narrow chest - Suguru Tatsuki; Makoto Hashimoto; Ryuji Koshima (Journal of Cardiothoracic Surgery)
Abstract Background Minimally invasive cardiac surgery for mitral regurgitation is challenging in patients with narrow chests due to limited thoracic space. The butterfly technique can prevent systolic anterior motion in patients with degenerative mitral regurgitation and redundant posterior leaflets, but it is difficult to perform via minimally invasive cardiac surgery. Few reports have described mitral valve repair using the butterfly technique or in a narrow chest. This case report demonstrates the feasibility and utility of robotically assisted mitral valve repair using the butterfly technique in a patient with a narrow chest, addressing the challenges involved through innovative port insertion and visualization. Case presentation A 70-year-old woman with a narrow chest (58 mm from spine to sternum) presented with shortness of breath on exertion. Transesophageal echocardiography revealed severe mitral regurgitation with posterior leaflet prolapse. Robotically assisted mitral valve repair was performed. Skin incisions were made in the third, fourth, and sixth intercostal spaces on the right anterior axillary line. A port for the atrial retractor was placed slightly medial to the right mid-clavicular line in the fifth intercostal space, inserted more shallowly than usual to achieve mitral valve exposure. The P2 leaflet was resected and reconstructed using the butterfly technique, followed by mitral annuloplasty with a semirigid partial band. The patient was discharged 6 days postoperatively with excellent valve function. One year later, she remained asymptomatic without obvious mitral regurgitation. Conclusions Robotically assisted mitral valve repair using the butterfly technique is feasible in patients with narrow chests. Robotic assistance facilitates mitral valve exposure and manipulation in challenging anatomical conditions through enhanced dexterity and visualization.